Copyright Management in Digital Content Marketing Strategy: A Perspective from Companies and Consumers in Sukoharjo Regency - Nugrohotomo, Gesang Kristianto; Sudalyo, Ramadhian Agus Triono; Prasetyaningrum, Nurita Elfani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to investigate the management of copyright in digital content marketing strategies from the perspectives of companies and consumers in Kabupaten Sukoharjo. Utilizing both qualitative and quantitative approaches, this research aims to provide a comprehensive understanding of the challenges, awareness, and practices related to copyright in the digital context. The research sample consists of 20 small and medium-sized companies actively using digital content marketing strategies in Kabupaten Sukoharjo, along with surveys conducted among consumers interacting with digital content from these companies. Qualitative data from interviews and document analysis will be thematically analyzed, while quantitative data from surveys will be analyzed using descriptive and inferential statistical techniques. The results of the study indicate that most companies have recognized the importance of managing copyright in digital content marketing strategies, although there is still variation in the implementation of policies and practices related to copyright. Consumers also have sufficient awareness of copyright, but there is still a small portion that pays less attention to copyright aspects in their interactions with digital content. In conclusion, this research highlights the need for further efforts to increase awareness and compliance with copyright, as well as collaboration between companies and consumers to create a more fair and ethical digital environment